2015
DOI: 10.1016/j.neuropsychologia.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The activation of visual face memory and explicit face recognition are delayed in developmental prosopagnosia

Abstract: Individuals with developmental prosopagnosia (DP) are strongly impaired in recognizing faces, but the causes of this deficit are not well understood. We employed event-related brain potentials (ERPs) to study the time-course of neural processes involved in the recognition of previously unfamiliar faces in DPs and in age-matched control participants with normal face recognition abilities. Faces of different individuals were presented sequentially in one of three possible views, and participants had to detect a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…This conclusion is in line with previous DP studies that investigated the activation of longer-term memory representations during the recognition of famous faces or previously learned target faces Parketny et al, 2015), and found that such recognition processes give rise to N250 components in participants with DP (see , for further discussion).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This conclusion is in line with previous DP studies that investigated the activation of longer-term memory representations during the recognition of famous faces or previously learned target faces Parketny et al, 2015), and found that such recognition processes give rise to N250 components in participants with DP (see , for further discussion).…”
Section: Discussionsupporting
confidence: 92%
“…During the successful recognition of familiar faces and of learned target faces, an enhanced negativity at lateral posterior electrodes emerges at around 250 ms after stimulus onset (Gosling & Eimer, 2011;Tanaka, Curran, Porterfield, & Collins, 2006). This N250 component, which is assumed to reflect the activation of a stored representation of a particular individual face in longer-term visual memory, has also been observed for individuals with DP Parketny, Towler, & Eimer, 2015). However, the N250 in response to a learned target face was delayed in DPs as compared to age-matched control participants (Parketny et al, 2015), suggesting that such identity matching processes are 5 triggered less rapidly in DP.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…While the ERP study by Eimer et al (2012) investigated the recognition of famous faces, which are likely to be represented in long-term memory, a recent experiment (Parketny, Towler, & Eimer, 2015) studied the processes that are responsible for the recognition of previously unfamiliar but now task-relevant faces in DP. In an experimental paradigm developed by Tanaka et al (2006), single face images were presented sequentially, and participants had to respond to a previously studied but otherwise unknown target face ("Joe"), while ignoring other task-irrelevant distractor faces.…”
Section: Erp Evidence For Delay and Disconnection In The Face Recognimentioning
confidence: 99%
“…In line with this hypothesis, reaction times to correctly detected target faces were about 150 ms slower in the DP group relative to the control group. The inclusion of participants' own faces in this study (Parketny et al, 2015) allowed us to investigate whether face-based self-recognition processes might also be impaired in DP. Overall, own faces elicited very similar N250 and P600f components in DPs and controls, suggesting that the activation of long-term representations of one's own face in visual memory and the subsequent explicit recognition of this face is not generally selectively impaired in DP.…”
Section: Erp Evidence For Delay and Disconnection In The Face Recognimentioning
confidence: 99%